Tanggung Gugat PPIU Terhadap Batalnya Perjalanan Ibadah Umrah Akibat Pandemi Covid-19 - Galang Pujo Sakti; Hervina Puspitosari (Universitas Widya Gama Malang, 2022)
Covid-19 is a non-natural national disaster stipulated by Presidential Decree No. 12 of 2020 concerning Disaster Declaration in the Spread of Corona Virus Disease 2019 (COVID-19) As a National Disaster. The Covid-19 pandemic caused the PPIU's (Umrah Service Organizing Committee) achievement to be carried out in the form of the implementation of the Umrah pilgrimage, which caused the PPIU to fail by default. This study uses a normative juridical research method, where the legal problems that occur will be analyzed by the authors using a statutory approach and literature study. The results of this study itself show that the failure of the departure of prospective Umrah pilgrims caused by the Covid-19 pandemic cannot be said to be a force majeure condition, because the Umrah travel agreement contained in the Decree of the Director General of Haji and Umrah Organization Number 323 of 2019 concerning guidelines for the registration of Umrah pilgrims did not explain for certain that the Covid-19 pandemic itself was said to be a force majeure condition, so that the PPIU continued to provide accountability without having to prove fault from the PPIU. The responsibility given is in the form of renegotiation between the PPIU and prospective pilgrims in the form of rescheduling the Umrah pilgrimage trip after the Covid-19 pandemic and refunding registration fees for prospective pilgrims who request cancellation with valid reasons. The legal consequence of this is that it is not allowed to unilaterally cancel the agreement on the grounds that Covid-19 is a force majeure condition, before the Government can provide certainty in terms of laws or policies related to the Covid-19 pandemic.